Sarah - Lazure, Sarah K (East Carolina University, 2017)
As a woman artist, I create my own places to exist. My self-portraits are full of emotion, thought, and creative energy and are made to engage the viewer in an intimate moment. I work by transforming thoughts and emotions into photographs and then alter the image. The creative process is an intuitive call and response between me and the materials. I continue to manipulate the surface until the discourse is complete and the piece is balanced. I empower my gaze and the intimacy of prolonged eye contact to portray the strength of my vulnerability and my desire to connect, acknowledge, and interact with my viewer. My gaze is commanding and requests your return gaze. There is no question that I am looking at you.
Keywords: photography; self; female gaze; creative process; Self-presentation in art; Gaze in art; Self-portraits